Covalent DNA Binding Is Essential for Gram-Negative Antibacterial Activity of Broad Spectrum Pyrrolobenzodiazepines - Pietro Picconi; Charlotte K. Hind; J. Mark Sutton; Khondaker Miraz Rahman (MDPI AG, 2022)
It is urgent to find new antibiotic classes against multidrug-resistant bacteria as the rate of discovery of new classes of antibiotics has been very slow in the last 50 years. Recently, pyrrolobenzodiazepines (PBDs) with a C8-linked aliphatic-heterocycle have been identified as a new broad-spectrum antibiotic class with activity against Gram-negative bacteria. The active imine moiety of the reported lead pyrrolobenzodiazepine compounds was replaced with amide to obtain the non-DNA binding and noncytotoxic dilactam analogues to understand the structure-activity relationship further and improve the safety potential of this class. The synthesised compounds were tested against panels of multidrug-resistant Gram-positive and Gram-negative bacteria, including WHO priority pathogens. Minimum inhibitory concentrations for the dilactam analogues ranged from 4 to 32 mg/L for MDR Gram-positive bacteria, compared to 0.03 to 2 mg/L for the corresponding imine analogues. At the same time, they were found to be inactive against MDR Gram-negative bacteria, with a MIC > 32 mg/L, compared to a MIC of 0.5 to 32 mg/L for imine analogues. A molecular modelling study suggests that the lack of imine functionality also affects the interaction of PBDs with DNA gyrase. This study suggests that the presence of N10-C11 imine moiety is crucial for the broad-spectrum activity of pyrrolobenzodiazepines.